The study on design and fabrication of a log periodic dipole array antenna for aviation industry / Mohd Hairi Selamat - Selamat, Mohd Hairi (2010)
Antenna is the device that is the heart of communication systems, being used to transmit and receive radio signals. An antenna forms the interface between the free space and the transmitter/receiver. The choice of a particular antenna depends on factors such as gain, radiation pattern, polarization, bandwidth, resonant frequency and impedance. In the last two decades, log periodic dipole arrays (LPDA's) have become the most popular commercial antennas for the reception of TV signals in the VHF and UHF bands in Europe. LPDA's have outnumbered Yagi-Uda antennas owing to their relatively simple construction and good broadband properties [3]. However, Yagi-Uda antennas typically have higher gain compared with LPDA's [3]. The LPDAs belongs to the class of wire antennas and commercial LPDAs consist of dipoles that are carried by a transmission line. An ideal LPDA consists of several symmetrical dipoles, whose dimensions form a geometric progression on a logarithmic scale. Normally, this antenna operates in the range from 900 MHz to 1400 MHz, which is within the operational range for aviation usage. In order to construct a simple construction, low cost and good broadband properties antennas, it was decided that only log periodic dipole arrays (LPDA's) antenna has been taken for further investigation. At the end of project, the LPDA antenna is design to start radiating at 900 MHz and stop its radiation at 1400 Mhz. This will give a bandwidth of 500 MHz